Towards optimized drum composting: evaluation of the radial mixing performance of a model substrate on the laboratory scale. Issue 12 (24th May 2020) - Schneider, Jonas; Burg, Jan Michael; Theilen, Ulf; Weigand, Harald; Brück, Felix
ABSTRACT: The rotating drum composter (RDC) is one of the most widespread reactor systems for biowaste treatment, worldwide. Nevertheless, knowledge on optimum operating conditions including, e.g. fill level, turning frequency, and mixing tool configuration is sparse. This study investigated the effect of static mixing tools (SMTs) on mixing in a rotating drum at high fill levels (60–80%). The methodological approach encompassed mixing experiments in a laboratory RDC using soaked wheat grains as a model material. The temporal course of material blending was quantified in terms of the entropy of mixing using digital image analysis. Experiments without SMTs showed the evolution of unmixed cores. With a single SMT, mixing was superior even at fill levels >70% while peripheral unmixed zones persisted when overly long SMTs were used. The results of this study may help to derive optimal process conditions for RDCs operated at high fill levels. GRAPHICAL ABSTRACT: